Sentenças aditivas e a superação do paradigma do legislador negativo - Correia, Clint Rodrigues (2015)
This paper aims at demonstrating the theoretical and practical surpass of the negative legislator as a paradigm employed by jurisprudence in the Supreme Federal Court, which gives way to access by technology to constitutional law in the so-called non-typical decisions, and in particular in additive judgments. The survey is based on an assumption of the inadequate argument brought about in rulings by the Brazilian Supreme Court with regard to the Court being unable to act as a positive legislator. Based on this statement, the outcome is the instrumental access by Constitutional Justice to the so-called non-typical and intermediate rulings. Special attention is dedicated to one of the types of such decisions the additive judgments by examining their conceptual restrictions and key features, chiefly as of their development by the Italian Constitutional Court, as well as some of the limits commonly detected by doctrine that justify their lawful use by the Constitutional Court. To this end the paper employed inductive and deductive methods and was based on bibliographical research of a descriptive and jurisprudential nature